Factors Related To The Use Of Contraceptional Equipment In Couples Of Reporting Age In The Village Pematang Biara Kecamatan Pantai Labu, Kabupaten Deli Serdang - Elsarika Damanik (Science Midwifery, 2021)
Indonesia is the fourth most densely populated Nation after China, India, and United States of America with 259 million people in 2016. Family Planning Program has high implication to health development quantitatively and qualitatively due to its strategic position in controlling the growth rate. The objective of the research was to discover the Factors Related to Contraceptive Use in PUS (Reproductive-Aged Couple) in Pematang Biara Village, Pantai Labu Subdistrict Deli Serdang Regency, in 2017. This is an analytical research with cross-sectional design. The research population was all PUS who domiciled in Pematang Biara Village i.e. 556 PUS and the samples were 100 respondents. The samples were taken by employing simple random sampling technique. It was discovered that 63 respondents (63%) used contraception and the other 37 respondents (37%) did not. The results indicated that there was a correlation of health personnel’s role (p= 0.008) and husband’s support (p= 0.000) with the contraceptive use. Meanwhile, age (p= 0.147), education (0.223), Parity (0.473), Culture/Belief (0.980), and health service (0.603) were not correlated with contraceptive use. It was concluded that there was a correlation of health personnel’s role and husband’s support with contraceptive use in pematang biara village, pantai labu sub district, deli serdang regency, in 2017. It was expected that the health personnel create effective counseling strategies to socialize contraceptive use by making husbands to participate in the socialization.